Association of dietary inflammatory index with sarcopenia in asthmatic patients: a cross-sectional study - Lin, Shuqiong; Su, Xia; Chen, Liqun; Cai, Zhiming (Frontiers in Nutrition, 2023)
Background: Sarcopenia is a complication of asthma, and asthmatics with sarcopenia are at an increased risk of poor prognosis. Anti-inflammatory intervention promising as an effective measure to prevent sarcopenia among patients with asthma. Diet is an important way to regulate inflammation throughout the body. The dietary inflammatory index (DII) is an index that assesses an individual's overall dietary inflammatory potential. The relationship between DII and sarcopenia among patients with asthma is not clear. Objective: To examine the correlation between DII and the sarcopenia among individuals with asthma Method: The National Health and Nutrition Examination Survey (NHANES) was the data source utilized in this study, spanning two time periods from 1999 to 2006 and 2011 to 2018. The study encompassed 3,389 participants in total. DII was calculated using the results of the participants' 24-hour dietary recall interviews. Patients were categorized into three groups based on the DII tertile: T1 group (n=1,130), T2 group (n=1,129) and T3 group (n=1,130). Logistic regression analysis, taking into account the NHANES recommended weights, was performed to assess the relationship between DII and sarcopenia.Result: After full adjustment, there was a significant positive correlation between DII levels and the risk of sarcopenia in asthmatic patients (OR: 1.27, 95% CI: 1.13 -1.42, P<0.001). Compared with T1 group, T3 group had higher risk of sarcopenia (T2: OR: